Determinants of young People’s gender norm attitudes related to rights and equity in Southeast Nigeria - Irene Ifeyinwa Eze; Chinyere Ojiugo Mbachu; Ozioma Nwankpa; Obinna Onwujekwe (Archives of Public Health)
Abstract Background Gender norms shape rights, privileges, and societal roles, impacting health and well-being. In low- and middle-income countries (LMICs), while young people may reject harmful gender discrimination, they often support other norms that perpetuate gender imbalances. This study examines factors influencing young people’s attitudes toward gender norms, focusing on men’s rights in decision-making, education, social roles, and equity for women’s empowerment in Southeast Nigeria. Methods A cross-sectional analytical study was conducted from October 2022 to March 2023 in six communities in Ebonyi State, Nigeria, with 1025 young people aged 15–24 selected using cluster sampling. Gender norm attitudes were assessed using a three-point Likert scale questionnaire. Mean scores exceeding 1.5 indicated favourability towards negative gender norms. Statistical analysis included univariate, bivariate, and multivariate linear regression with statistical significance set at a p < 0.05. Results Over 60% of participants believed that men should have more decision-making power than women, but fewer than 30% supported unequal access to education for boys. More than two-thirds endorsed women/girls’ empowerment. Predictors of support for men’s decision-making rights, education, and protective rights included schooling status (β = -1.896, p < 0.001), educational status (β = 5.593, p = 0.004), gender (β = 0.529, p < 0.001), mother’s educational level (β = 1.993, p = 0.020), household leadership (β = 0.218, p = 0.003) and religion: β = -0.175, p = 0.008). Predictors of support for women’s empowerment included gender (β = 10.299, p < 0.001), schooling status (β = -0.170, p = 0.012), and father’s educational level (β = -0.212, p = 0.041). Conclusion Despite widespread support for gender equality for women’s empowerment, young people in the Southeast still favour traditional gender norms, particularly decision-making and educational rights for men. Factors such as educational status, gender, and household leadership play a significant role in shaping these attitudes. Interventions that promote gender equity should focus on education, challenge traditional norms, and engage both young men and women in discussions about shared decision-making and equal access to opportunities.